Biomimetic scaffolds produced by robocasting for bone regeneration: evaluation of structural and chemical features - Baltazar, Catarina Salgueiro (2023)
Bone diseases such as osteoporosis and osteomyelitis, as well as degenerative and cancerous diseases of bone tissue, are increasingly common. In order to find alternative solutions to the traditional ones for bone tissue regeneration, the objective of this work is to manufacture self-hardening composite scaffolds for bone replacement with high concentrations of calcium phosphates, improved biological performance and adequate mechanical properties without resorting to the sintering process (normally used in ceramic products), through the additive manufacturing technique known as robocasting. To achieve this goal, (1) calcium phosphate powders doped with different doping concentrations of ions naturally present in native bone were synthesized, (2) reactive composite pastes were developed with a high concentration of calcium phosphate-based powders incorporated in a polymeric matrix, and (3) self-hardening hydroxyapatite composite scaffolds were produced. β-tricalcium phosphate powders non-doped, single-doped and multi-doped with manganese, magnesium, strontium, and zinc were synthesized by chemical precipitation in aqueous medium and calcined at 1000 ºC. Ion contents (1) within the recommended and non-toxic values and (2) 10 times higher than the previous ones were used. After structural and biological characterization of the doped powders, they were used in the preparation of self-hardening injectable pastes starting from composite matrices based on a mixture of α-TCP and β-TCP powders, and pluronic F127. After rheological studies of viscometry and viscoelasticity of the pastes, they were used to produce scaffolds by robocasting. The scaffolds obtained were characterized for their mechanical, microstructural, and biological performance. From the results obtained, and compared to previous studies, it was found that the combination of ionic species and the use of doping values higher than those recommended in β- tricalcium phosphate powders did not show cytotoxic effects. With adequate mechanical properties, the multi-doped scaffolds obtained in this work showed improved biological properties, suggesting that they are very promising as bone substitutes for bone regeneration.